2011
DOI: 10.6004/jnccn.2011.0073
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Therapy of Esophageal Premalignancy and Early Malignancy

Abstract: Esophageal adenocarcinoma (EAC) is an often deadly cancer with a rising incidence in Western countries. Chronic gastroesophageal reflux disease is associated with the metaplastic transformation of normal squamous epithelium to premalignant specialized intestinal metaplasia within the esophagus (Barrett's esophagus). Barrett's esophagus may progress to low-grade dysplasia (LGD), high-grade dysplasia (HGD), or even EAC. Although nondysplastic Barrett's esophagus progresses to EAC at a rate of 0.5% per year, rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…The strongest evidence for the effectiveness of photodynamic therapy derives from a prospective, randomized study in which, after a five years' follow-up, a significant difference was shown between a group of patients treated with photodynamic therapy plus omeprazole vs. a group treated with omeprazole alone. In this study, the percentage of ablation in high grade dysplasia was 77% vs. 39% (p=0.004), whereas the recurrence of neoplasia was 15% vs. 29% (p=0.027) (75). The occurrence of esophageal stenosis is a relatively frequent adverse event of photodynamic therapy (27-34% of cases), which typically develops within one month (76).…”
Section: Treatmentmentioning
confidence: 60%
See 1 more Smart Citation
“…The strongest evidence for the effectiveness of photodynamic therapy derives from a prospective, randomized study in which, after a five years' follow-up, a significant difference was shown between a group of patients treated with photodynamic therapy plus omeprazole vs. a group treated with omeprazole alone. In this study, the percentage of ablation in high grade dysplasia was 77% vs. 39% (p=0.004), whereas the recurrence of neoplasia was 15% vs. 29% (p=0.027) (75). The occurrence of esophageal stenosis is a relatively frequent adverse event of photodynamic therapy (27-34% of cases), which typically develops within one month (76).…”
Section: Treatmentmentioning
confidence: 60%
“…The introduction of new endoscopic treatments characterized by a lower incidence of complications, including the risk of lymphatic or hematogenous dissemination, has reduced the indications of surgery to patients with high grade dysplasia or early AC (74,75). The endoscopic procedures, either by resection or by ablation of the inner lining of the esophagus, usually result in regenerated squamous epithelium.…”
Section: Treatmentmentioning
confidence: 99%
“…The discussion led to the following shared statement [34][35][36][37]: Consensus Statement 10: The Working Group recommends that patients with BE with a diagnosis of HGD/IMC (confirmed by a pathologist) are treated, in the absence of visible lesions, with targeted EMR in the area where the HGD/IMC is suspected based on the mapping biopsy, plus RFA; alternatively only with RFA.…”
Section: Resultsmentioning
confidence: 99%
“…Over the decades, esophagectomy with lymph node (LN) dissection has remained the most effective treatment modality for patients with early-stage ESCC (6,7). Adequate lymph nodes harvested, esophagectomy might increase postoperative morbidity and mortality which is probably unsuitable for patients with suspected T1N0M0 disease (8)(9)(10). In recent years, endoscopic resection (ER), however, exhibits great potential in treating small-sized T1 disease, which might be alternative to conventional esophagectomy (11).…”
Section: Bcakgroundmentioning
confidence: 99%